Plasma-cathode electron source based on a low-pressure arc discharge in the mode of the emission current enhancement; High Temperature Material Processes: An International Quarterly of High-Technology Plasma Processes; Vol. 19, iss. 1 - Koval T. V. Tamara Vasilievna; Devyatkov V. N. Vladimir Nikolaevich; Nguyen Bao Khyng; Uglov V. V. Vladimir Vasilievich (2015, 2015)
Title screen